IMITATION MODEL OF A HIGH-SPEED INDUCTION MOTOR WITH FREQUENCY CONTROL - V. E. Pliugin (National Technical University "Kharkiv Polytechnic Institute", 2017)
Purpose. To develop the imitation model of the frequency converter controlled high-speed induction motor with a squirrel-cage rotor in order to determine reasons causes electric motor vibrations and noises in starting modes. Methodology. We have applied the mathematical simulation of electromagnetic field in transient mode and imported obtained field model as an independent object in frequency converter circuit. We have correlated the simulated result with the experimental data obtained by means of the PID regulator factors. Results. We have made the simulation model of the high-speed induction motor with a squirrel-cage rotor speed control in AnsysRMxprt, Ansys Maxwell and Ansys Simplorer, approximated to their physical prototype. We have made models modifications allows to provide high-performance computing (HPC) in dedicated server and computer cluster to reduce the simulation time. We have obtained motor characteristics in starting and rated modes. This allows to make recommendations on determination of high-speed electric motor optimal deign, having minimum indexes of vibrations and noises. Originality. For the first time, we have carried out the integrated research of induction motor using simultaneously simulation models both in Ansys Maxwell (2D field model) and in Ansys Simplorer (transient circuit model) with the control low realization for the motor soft start. For the first time the correlation between stator and rotor slots, allows to obtain minimal vibrations and noises, was defined. Practical value. We have tested manufactured high-speed motor based on the performed calculation. The experimental studies have confirmed the adequacy of the model, which allows designing such motors for new high-speed construction, and upgrade the existing ones.